ROMA COMMUNITY IN ALBANIA BEFORE AND AFTER THE PERIOD OF COMMUNISM - Osmanaj, Elisabeta (European Scientific Journal, ESJ, 2013)
This article aims to provide information about living, economic level, place of living and the education of the Rome ethnic minority in Albania. In fact, Rome population have lived in poor condititions, even though in communist period were followed different policies, the priorities of those policies were the raise of education services and living conditions. Based on their origin they used to wander through different places without having a permanent residence for a long period of time. There are several hypotheses for their origin and their language. They were supposed to move to west in XI century and settled in Balkan in XIV century, as well as were supposed that they were placed in Albania in XV/XVI century. In different documents and archives there are no exact data on the number of Rome but it is thought to be around 30,000 - 120,000 people in total minority. The lack of accurate statistics has been and it is a major obstacle for studying and analyzing the situation of the community. During the communist policies was supposed that citizens should have equal rights, be educated, to vote, to have permanent residence and better living conditions. Also at that time education was obligatory for the whole population, without exception, and during this time the number of Roma population attending compulsory education was almost the same as the rest of the population and the number of illiterates among Roma was low. Instead, after 90 years, the policies pursued by the state are critical and does not support this minority and not recognized as minimum rights Convention on Human Rights, to which so much discussed in international higher instances. Nobody cares about their economy, the right to vote or the right legitimate to education. Roma are themselves wanting to win their rights have set up organizations that protect their existence by force and send their voice internationally. Roma are isolated throughout Albania, few of them live in good conditions, most live in very difficult conditions, being forced to do hard work to make a living and have no opportunity to attend school or education.